Initialisms in Scientific Writing in the 19th and Early 20th Centuries - Katrin Menzel (Zeitschrift für Wortbildung)
This paper focusses on the role of initialisms in scientific English articles in the Royal Society Corpus (Fischer et al. 2020; Kermes et al. 2016). The development of scientific initialisms is illustrated with frequency data, a discussion of the evolution of the text topics obtained from topic modelling and an analysis of the development of information-theoretic surprisal values of initialisms in three time spans between 1830 and 1919. The overall frequency and diversity of initialisms for scientific concepts has risen considerably between 1830 and 1919 in the context of the ongoing specialisation of the sciences. Particularly from the 1860s onwards scientific initialisms increasingly become shortcuts for multiword units with wordhood and term status. The surprisal values of scientific initialisms decrease over time as such forms more regularly occur in conventionalised textual contexts and fixed expressions. Overall, the analysis of the RSC texts shows that key developments towards the conventionalisation of scientific initialisms as term formation patterns took place in the transitional period from Late Modern to Present-day English.